STUDY ON RUMPUT MUTIARA (Hedyotis Corimbosa) HERBS AS MEDICINE - Andreanus A. Soemardji; Ita N. Anisa; Nareswari Alka Damayanti (Journal of Medicine and Health, 2015)
â€œRumput Mutiaraâ€ or Pearl grass (Hedyotis corymbosa) is one of medicinal plants used empirically by the Indonesian people to cure disease to maintain health. Many people have used pearl grass for a long time. This plant contains hentriacontane, stigmasterol, ursolic acid, oleanolicacid, Î²-sitosterol, sitisterol-D-glucoside, p-coumaric acid, flavonoid-glycosides, â€œbaihua she she cao suâ€ (possibility coumarin analog), iridoid glycosides, alizarin, korogenin, and bonding antragalol.Â  Herbaceous plant is used and effetive as a relieve fever (antipyretic), anti-inflammatory, antibacterial, laxative urine(diuretic), removes heat and toxins (detoksikan), blood circulation, anti-cancer, the treatment of peptic ulcers, dysentery, exhausted maternity, and indigestion. This review article is a compilation of Hedyotis corymbosa herb as traditional medicinal plant and pharmacological researches of this herb that can be use as ethnopharmacological and pharmacological information of this medicinal herb.Â Keywords: Â Pearl grass, Hedyotis corymbosa, medicinal plants, ethnopharmacology, pharmacology.